USAHA PRODUK MINYAK VIRGIN COCONUT OIL (VCO) DARI KELOMPOK WANITA TANI SEKAR JEPUN DI DESA TENGKUDAK - I Gusti Ngurah Satria Wijaya; I Wayan Kayun Suwastika; Komang Budi Mas Aryawan; Resa Sigit Ardiyanto; Alang Pandu Dewanata (Denpasar Institute, 2019)
Sekar Jepun Women's Farmers Group (KWT) located in Tengkudak village, Penebel District, Tabanan Regency, is a productive business group formed in 2010 by the PKK in Tengkudak village. One of the products produced is Bali Luwih Virgin Coconut Oil (VCO). The main problem of the Sekar Jepun VCO KWT business besides the production process is promotion or marketing. The solutions provided include providing marketing media in the form of signage, websites, website updates, and marketing media training through social media. In addition, financial management training was provided in the form of recording business expenses and revenues. Equipment assistance was provided in the form of coconut extraction machines and coconut milk extracting machines so that production is faster and more. The main work procedures of community service activities are started from socialization activities, then increase production, improve marketing technology through websites and social media, and financial management. The results of empowerment are expected to increase orders so as to increase production and income of Sekar Jepun's KWT.